Kontribusi Laboratorium Kimia dan Sikap Siswa terhadap Pemanfaatan Laboratorium terhadap Keterampilan Berpikir Kritis dan Kreatif - Novrita Mulya Rosa; Fatwa Patimah Nursa'adah (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2017)
The purpose of this research is to analyze the contribution of chemistry laboratory and student attitudes toward the utilization of chemistry laboratory toward critical and creative thinking skill. Subjects of students of class XI SMAN 66 in Cilandak, South Jakarta. Selection of sample class using random sampling technique. Analysis of research data using MANOVA. From the results of the study concluded that (1) there is influence of laboratory contribution to critical and creative thinking skill; (2) there is influence of attitude toward laboratory utilization on critical thinking and creative thinking skill; (3) there is no interaction between laboratory contributions and attitudes towards laboratory utilization of critical thinking and creative thinking skill.